3D Anisotropic Polyethylene as Light‐Responsive Grippers and Surfing Divers. (24th February 2021) - Pan, Xinglong; Grossiord, Nadia; Sol, Jeroen A. H. P.; Debije, Michael G.; Schenning, Albert P. H. J.
Abstract: Untethered soft actuators are usually based on 3D engineered special polymers such as liquid crystal networks or hydrogels that require complex fabrication methods. Here, an easy‐to‐process, anisotropic composite soft actuator based on a simple photothermal dye‐doped polyethylene film is presented. The 3D anisotropic polymer films are prepared by solution‐casting and subsequent thermal solid‐stretching. The resulting soft actuators exhibit large and controllable bending in response to light (UV and/or near‐infrared (NIR)) and are able to act as grippers picking up cargo. Additionally, the films are capable of realizing "diving" and "surfing" locomotion in and over a liquid via the photothermal induced Marangoni effect, yielding a NIR light‐fueled transporter able to pick up cargo. The results open up new possibilities of using commodity polymers in a broad range of applications including untethered soft actuators and robotic devices. Abstract : 3D anisotropic single‐layer polyethylene composite films are fabricated. Such films can be used to fabricate light‐responsive actuators, grippers, surfers, and transporters. This work opens up innovative possibilities to use commodity polymers in a broad range of applications such as untethered soft actuators and robotic devices.